2006
DOI: 10.1088/0964-1726/15/3/n03
|View full text |Cite
|
Sign up to set email alerts
|

A real-time active smart patch system for monitoring the integrity of bonded repair on an aircraft structure

Abstract: There currently exists a need to develop a cost-effective, in-service structural health monitoring (SHM) system for determining the initial quality of a bonded repair and assessing the long-term durability of the bonded repair on an aircraft structure. In this paper, a real-time active smart patch system (SPS) based on SMART layer technology is introduced for monitoring the integrity of bonded repairs. First, an overview of the SPS is given for typical metal and composite repairs. To illustrate the capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The SMART Layer technology can offer a state of the art solution to the current problems associated with the structural inspection and safety of high value military assets. It can be applied to a variety of accessible and inaccessible structures with complex geometries [4][5][6][7][8][9][10]. However, a major drawback of the existing technology for real-time Structural Health Monitoring (SHM) is the requirement for external electrical power input from the vehicle power system.…”
Section: Introductionmentioning
confidence: 99%
“…The SMART Layer technology can offer a state of the art solution to the current problems associated with the structural inspection and safety of high value military assets. It can be applied to a variety of accessible and inaccessible structures with complex geometries [4][5][6][7][8][9][10]. However, a major drawback of the existing technology for real-time Structural Health Monitoring (SHM) is the requirement for external electrical power input from the vehicle power system.…”
Section: Introductionmentioning
confidence: 99%
“…Detection Diagnostic, b. Damage Location [2], c. Damage Occurrence [3], d. Damage extent and e. Damage Quantification [3,4]. A great amount of research activity in this area can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Active wave propagation using piezoelectric sensors and actuators has been demonstrated to be effective for monitoring FRP materials. Sensor/actuator pairs have been integrated into surface bonded sensor patches (Cheng and Taheri, 2005), surface mounted wafer sensors (Giurgiutiu et al, 2003) and polyimide layers that are then embedded between individual laminae (Lin et al, 2001;Qing et al, 2006;Wu et al, 2006). While active wave propagation can provide accurate information on the integrity of the strengthening system, high density sensor/actuator pairs are required due to the short propagation distance of the excited waves.…”
Section: Introductionmentioning
confidence: 99%